(untitled) (Nóema, 2019)
My article focuses on the status of the materialist dialectic in Sartre, with particular reference to the second part of the Critique of Dialectical Reason, with the points of continuity and together with the lines of demarcation with respect to Marxism. The attempt is to keep together, albeit in an unstable manner, the investigation into the intelligibility of History with an approach that takes on the demands of Marxian materialism, with a strong enhancement of the political dimension of the struggles, but within the specific space of the situation.